Making Capitalism Work: Social Capital and Economic Growth in Italy, 1970-1995 - Thomas P. Lyon (Fondazione Eni Enrico Mattei (FEEM), 2005)
Using data on the 20 Italian regions for the period 1970-1995, I examine whether the presence of social capital, as reflected in a number of different measures collected by Putnam (1993), affects economic productivity. I find three types of effects. First, social capital, when treated as an input to regional production, has a positive and significant effect in the South, but a much weaker effect in the North. Second, some forms of social capital can significantly increase regions propensities to make physical capital investments; however, dense networks of association reduce capital investment in both the North and South. Instrumental variables estimates show that social capital affects growth both directly and through affecting investment in physical capital. Third, social capital contributes positively to the rate of total factor productivity growth in the Italian regions.
Keywords: O17; O47; O52; 330; Social capital; Growth; Investment; Italy